A novel cuproptosis-related gene signature for predicting prognosis in cervical cancer - Lei, Lei; Tan, Liao; Sui, Long (Frontiers in Genetics, 2022)
Purpose: Cuproptosis, a copper-induced cell death, can be a promising therapeutic target for refractory cancers. Hence, we conduct this research to explore the association between cuproptosis and prognosis in Cervical cancer (CC). Methods: For constructing a prognostic signature based on the cuproptosis-related genes from the TCGA database, a least absolute shrinkage and selection operator Cox regression was utilized. The GSE44001 cohort was utilized for validation. Results: Nine cuproptosis-related genes showed distinct expression in CC and normal samples in the TCGA-GTEx cohort. Two risk groups were identified based on a seven-gene signature. A significant decrease in overall survival was observed in the high-risk group (P < 0.001). The risk score (HR = 2.77, 95%CI = 1.58-4.86) was an autocephalous predictor with better predictive ability than the clinical stage. Functional analysis indicated that immune activities were suppressed in the high-risk group than in the low-risk group. Eleven candidate compounds targeting the signature were identified. Conclusions：The seven cuproptosis-related genes signature were construct to predict prognosis and propose a new therapeutic target for patients with CC.